Psychiatry and the Sociology of Novelty: Negotiating the US National Institute of Mental Health "Research Domain Criteria" (RDoC). (July 2019) - Pickersgill, Martyn
In the United States, the National Institute of Mental Health (NIMH) is seeking to encourage researchers to move away from diagnostic tools like the Diagnostic and Statistical Manual of Mental Disorders (the DSM ). A key mechanism for this is the "Research Domain Criteria" (RDoC) initiative, closely associated with former NIMH Director Thomas Insel. This article examines how key figures in US (and UK) psychiatry construct the purpose, nature, and implications of the ambiguous RDoC project; that is, how its novelty is constituted through discourse. In this paper, I explore and analyze these actors' accounts of what is new, important, or (un)desirable about RDoC, demonstrating how they are constituted through institutional context and personal affects. In my interviews with mental health opinion leaders, RDoC is presented as overly reliant on neurobiological epistemologies, distant from clinical imaginaries and imperatives, and introduced in a top-down manner inconsistent with the professional norms of scientific research. Ultimately, the article aims to add empirical depth to current understandings about the epistemological and ontological politics of contemporary (US) psychiatry and to contribute to science and technology studies (STS) debates about "the new" in technoscience. Accordingly, I use discussions about RDoC as a case study in the sociology of novelty.